(A Literature Review) Re-examining issues behind the loss of family and cultural and the impact on Aboriginal youth suicide rates - Morris, Kristine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This paper examines child welfare issues in relation to the impact of cultural loss and/or lack of cultural identity and its correlation with suicide risk among young Aboriginal persons.